A Comprehensive Numerical Study of the Behaviour of an LH2 Storage Tank in the Event of a Fire - Aliasghar Hajhariri; Robert Eberwein; Davide Camplese; Giordano Emrys Scarponi; Frank Otremba; Valerio Cozzani; Holger Seidlitz (Chemical Engineering Transactions)
As the world moves towards green energy production, effective storage and transportation solutions become essential. To support this transition, energy carriers with minimal or zero environmental impact are required. Liquified hydrogen represents a promising candidate due to its emissions-neutral properties. However, its highly flammable nature necessitates adherence to strict safety codes and standards. Storing hydrogen often requires advanced super-insulation materials. To enhance the safety of cryogenic hydrogen storage tanks under extreme conditions, such as those encountered during fire accidents, it is crucial to understand the thermal behaviour of the tank. Predicting pressurization and potential failure in advance demands a robust and comprehensive model. However, still such models suffer lack of detailed heat transfer models which account for various sub-processes during an accident scenario. Hence, this study introduces a comprehensive model for the pressurization of cryogenic tanks equipped with multi-layer insulation (MLI) systemsin the event of fire, which comprises several sub-models. These sub-models account for heat transfer phenomena through the thermal insulation at nominal conditions and its thermal degradation during fire exposure, the fluid, the internal pressurization, and the performance of the pressure relief valve. This study provides valuable insights into the safety and the behaviour of hydrogen storage tanks under thermal loads.